Social Norms and Financial Incentives to Promote Employees’ Healthy Food Choices: A Randomized Controlled Trial - Thorndike, Anne N. (Prev Med, 2016)
Population-level strategies to improve healthy food choices are needed for obesity prevention. We conducted a randomized controlled trial of 2,672 employees at Massachusetts General Hospital who were regular customers of the hospital cafeteria with all items labeled green (healthy), yellow (less healthy), or red (unhealthy) to determine if social norm (peer-comparison) feedback with or without financial incentives increased employees’ healthy food choices. Participants were randomized in 2012 to three arms: 1) monthly letter with social norm feedback about healthy food purchases, comparing employee to “all” and to “healthiest” customers (feedback-only); 2) monthly letter with social norm feedback plus small financial incentive for increasing green purchases (feedback-incentive); or 3) no contact (control). The main outcome was change in proportion of green-labeled purchases at end of 3-month intervention. Post-hoc analyses examined linear trends. At baseline, the proportion of green-labeled purchases (50%) did not differ between arms. At end of the 3-month intervention, the percentage increase in green-labeled purchases was larger in the feedback-incentive arm compared to control (2.2% vs. 0.1%, P=0.03), but the two intervention arms were not different. The rate of increase in green-labeled purchases was higher in both feedback-only (P=0.04) and feedback-incentive arms (P=0.004) compared to control. At end of a 3-month wash-out, there were no differences between control and intervention arms. Social norms plus small financial incentives increased employees’ healthy food choices over the short-term. Future research will be needed to assess the impact of this relatively low-cost intervention on employees’ food choices and weight over the long-term. Trial Registration: Clinical Trials.gov NCT01604499